Proteasome subunit PSMC3 variants cause neurosensory syndrome combining deafness and cataract due to proteotoxic stress - Ariane Kröll‐Hermi; Frédéric Ebstein; Corinne Stoetzel; Véronique Geoffroy; Elise Schaefer; Sophie Scheidecker; Séverine Bär; Masanari Takamiya; Koichi Kawakami; Barbara A Zieba; Fouzia Studer; Valerie Pelletier; et al. (EMBO Molecular Medicine)
Abstract The ubiquitin–proteasome system degrades ubiquitin‐modified proteins to maintain protein homeostasis and to control signalling. Whole‐genome sequencing of patients with severe deafness and early‐onset cataracts as part of a neurological, sensorial and cutaneous novel syndrome identified a unique deep intronic homozygous variant in the PSMC3 gene, encoding the proteasome ATPase subunit Rpt5, which lead to the transcription of a cryptic exon. The proteasome content and activity in patient's fibroblasts was however unaffected. Nevertheless, patient's cells exhibited impaired protein homeostasis characterized by accumulation of ubiquitinated proteins suggesting severe proteotoxic stress. Indeed, the TCF11/Nrf1 transcriptional pathway allowing proteasome recovery after proteasome inhibition is permanently activated in the patient's fibroblasts. Upon chemical proteasome inhibition, this pathway was however impaired in patient's cells, which were unable to compensate for proteotoxic stress although a higher proteasome content and activity. Zebrafish modelling for knockout in PSMC3 remarkably reproduced the human phenotype with inner ear development anomalies as well as cataracts, suggesting that Rpt5 plays a major role in inner ear, lens and central nervous system development.